Ten thousand Crores - Chopra, Sanjeev (Dehradun, 2004)
Uttaranchal is often identified with the lofty Himalayas, the mighty Ganga, awesome glaciers, alpine meadows, educational institutions, trekking expeditions, river rafting, old world cantonments, yoga Kendras, ashrams, pilgrim centres, eco-tourism, wild life and shikar tales. It is home to authors and poets, retired generals and bureaucrats, and Dehra Dun is also known as a city of many bookshops and a culturally vibrant place.
Keywords: Industrialisation-Uttaranchal